The Kurdish question in Syrian War: Domestic dynamics and regional impacts - Nasser, Reginaldo Mattar (2019)
The characteristics that qualify the Kurdish identity have long been recognized among its members, but the ability to form politically organized groups among them has varied throughout history. In order to understand the complexity of the Kurdish question in the Middle East, it is necessary to analyze the way in which they organize themselves politically, taking into account their ideologies, particularities of the State in which they find themselves, and, most of all, the political tensions and internal disputes of their movements. In addition to that, it is essential to insert Kurds' claim on autonomy in the context of the evolution of the civil war in Syria in a broader sense, as this is one of the main reasons for the growing involvement of Turkey and the great powers in the region.